If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(3p + 17) = -5 Reorder the terms: -3(17 + 3p) = -5 (17 * -3 + 3p * -3) = -5 (-51 + -9p) = -5 Solving -51 + -9p = -5 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '51' to each side of the equation. -51 + 51 + -9p = -5 + 51 Combine like terms: -51 + 51 = 0 0 + -9p = -5 + 51 -9p = -5 + 51 Combine like terms: -5 + 51 = 46 -9p = 46 Divide each side by '-9'. p = -5.111111111 Simplifying p = -5.111111111
| 3x+(5x-3)=7 | | 3(2x-5)+6(x+2)= | | 5x+3=x+31 | | 3+.5x=17-3x | | lx+6l=9 | | -4=w-30 | | 10+2x=15+1x | | 8y-3=6y+7 | | 96+12x+30=180 | | x*5-2x=38 | | a+5a=2a+9 | | A=.05bcd+bc | | 4+5x=x+23 | | t+28=13 | | a+5a=2a+a | | -6-3=3x+6-6 | | 1y-2=.33(y+6) | | 9=9-8h | | 5x-1y=15 | | 48+4y-18=14y-12-4y | | X+24=32X | | 3a^2+9a+12=0 | | 4k+8-6k= | | x+x=6+2 | | r(r+3)=0 | | 2y=82 | | 3a^2+9a-12=0 | | 1963-5x=1863 | | n+6/21=4/7 | | 3x+1(-2x+9)=7 | | 36-2(6-2x)=-16 | | n+15=3l |